Perancangan Jaringan Closed Circuit Television ( CCTV ) Berbasis Online Sebagai Monitoring Pada SDN 4 Praya - Sita Susilawati; Maulana Ashari (LPPM STMIK Lombok, 2018)
Technology that becomes main system that is utilized good at institution, firm and even at schools was beginning apply technology purpose to water down well that of security, monitoring, information access even system security utilizing technology, so one institution, firm and even school have more security system maximal. SDN 4 PRAYA gets initiative to want utilize technologies in learning system at within class, so student and schoolgirl gets at monitoring with far distance and also near in teaching and learning process that be happens. But technology what applicable for memonitoring teaching and learning activity at within class. What can at monitoring processes distance teaching and learning go away. On this research, researcher has done data collecting method and applies analisis's method, of that result, researcher has gotten one solution for design of Network CCTV gets Online basis as Monitoring On SDN 4 Praya. CCTV'S Network implementation gets online basis on eventually get as been applied SDN'S monitoring 4 Praya With be applied CCTV gets online basis, can know happening teaching and learning process within class and CCTV'S performance form online good of peripheral facet can be known. With implementations supportive specification monitoring can thru access distance goes away.